2004
DOI: 10.1021/la049515k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phloretin on the Dipole Potential of Phosphatidylcholine, Phosphatidylethanolamine, and Phosphatidylglycerol Monolayers

Abstract: The effect of phloretin on the potential of phosphatidylcholine (PC), phosphatidylethanolamine (PE,) and phosphatidylglycerol (PG) monolayers below and above the phase transition in mixtures of different PC/PE ratios with and without cholesterol of ester and ether phospholipids have been determined. The effectiveness of phloretin to decrease the dipole potential of monolayers in the fluid state is lessened by the moieties esterified to the phosphate group in the sequence choline > ethanolamine > glycerol. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…This tendency is related, at least in part, to the lipid shape (as is intuitive); for example, large headgroups and short tails normally increase the propensity to curl away from the water phase (forming for example micellar structures), whereas small headgroups and long tails tend to increase the desire to bend towards the water phase (forming “inverse” phases). Regarding the dipole potential, its experimental estimate [86], [87] could be reproduced by adjusting the magnitude of the glycerol and ester point dipoles, and the rigidity of the dipole orientation-restraining potential (equation 10).…”
Section: Methodsmentioning
confidence: 99%
“…This tendency is related, at least in part, to the lipid shape (as is intuitive); for example, large headgroups and short tails normally increase the propensity to curl away from the water phase (forming for example micellar structures), whereas small headgroups and long tails tend to increase the desire to bend towards the water phase (forming “inverse” phases). Regarding the dipole potential, its experimental estimate [86], [87] could be reproduced by adjusting the magnitude of the glycerol and ester point dipoles, and the rigidity of the dipole orientation-restraining potential (equation 10).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the decrease by phloretin of the dipole potential in phosphatidylcholine (PC) monolayers is more significant in the less hydrated gel state than in fluid state. This effect was attributed to neutralization or reorientation of dipole moieties at the interface others that the acyl chain carbonyl groups, since results obtained with ether-linked DMPC were similar to those obtained with esther-linked DMPC (Lairion and Disalvo 2004). More recently, Efimova and Ostroumova (2012) studied the effect of phloretin and other dipole modifiers on the magnitude of the dipole potential of planar bilayers composed by different phospholipid and sterols mixtures at room temperature.…”
Section: Introductionmentioning
confidence: 79%
“…At higher cholesterol concentrations, the capability of the sterol of promoting a liquid-ordered phase would decrease the effectiveness of phloretin as dipole potential modifier as a consequence of a reduced possibility of formation of hydrogen bonds between hydroxyls of phloretin and the phospholipids' P=O group (Ostroumova et al 2013). It has also been reported (Lairion and Disalvo 2004) that phloretin is more effective in reducing the dipole potential of DMPC monolayers in gel phase (from 515 to 270 mV) than in the liquid phase (from 449 to 297 mV). The increase in the affinity of DMPC and DPPC LUVs in the gel phase for ANS reported here can be explained by postulating that phloretin simply adsorbs to bilayers in the gel phase as it does to monolayers at high surface pressures (Cseh and Benz 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations